Antimicrobial and toxicological activities of five medicinal plant species from Cameroon Traditional Medicine - Njouendou Abdel J; Asongalem Emmanuel A; Nde Peter F; Njunda Anna L; Nsagha Dickson S; Kamga Henri LF; Assob Jules CN; Sandjon Bertrand; Penlap Veronique B (BMC, 2011)
Abstract Background Infectious diseases caused by multiresistant microbial strains are on the increase. Fighting these diseases with natural products may be more efficacious. The aim of this study was to investigate the in vitro antimicrobial activity of methanolic, ethylacetate (EtOAc) and hexanic fractions of five Cameroonian medicinal plants (Piptadeniastum africana, Cissus aralioides, Hileria latifolia, Phyllanthus muellerianus and Gladiolus gregasius) against 10 pathogenic microorganisms of the urogenital and gastrointestinal tracts. Methods The fractions were screened for their chemical composition and in vivo acute toxicity was carried out on the most active extracts in order to assess their inhibitory selectivity. The agar well-diffusion and the micro dilution methods were used for the determination of the inhibition diameters (ID) and Minimum inhibitory concentrations (MIC) respectively on 8 bacterial species including two Gram positive species (Staphylococcus aureus, Enterococcus faecalis), and six Gram negative (Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, Proteus mirabilis, Shigella flexneri, Salmonella typhi) and two fungal isolates (Candida albicans, Candida krusei). The chemical composition was done according to Harbone (1976), the acute toxicity evaluation according to WHO protocol and the hepatic as well as serum parameters measured to assess liver and kidney functions. Results The chemical components of each plant's extract varied according to the solvent used, and they were found to contain alkaloids, flavonoids, polyphenols, triterpens, sterols, tannins, coumarins, glycosides, cardiac glycosides and reducing sugars. The methanolic and ethylacetate extracts of Phyllanthus muellerianus and Piptadeniastum africana presented the highest antimicrobial activities against all tested microorganisms with ID varying from 8 to 26 mm and MIC from 2.5 to 0.31 mg/ml. The in vivo acute toxicity study carried out on the methanolic extracts of Phyllanthus muellerianus and Piptadeniastrum africana indicated that these two plants were not toxic. At the dose of 4 g/kg body weight, kidney and liver function tests indicated that these two medicinal plants induced no adverse effect on these organs. Conclusion These results showed that, all these plant's extracts can be used as antimicrobial phytomedicines which can be therapeutically used against infections caused by multiresistant agents. Phyllanthus muellerianus, Piptadeniastum africana, antimicrobial, acute toxicity, kidney and liver function tests, Cameroon Traditional Medicine